The cultural effect on emotion and emotional regulation in human service organisations: A case study on child and family workers - Ibrahim, Habibie; Johnson, Sally; Gilligan, Philip (2014)
The present research aimed to investigate the use of emotions and emotional regulation in child and family practice in a Malaysian context.The interrelationship between emotion and emotional regulation and cultural context were explored.The overall research strategy was ethnographic.The researchers used a mixture of methods including individual interviews, participant observation, and a questionnaire.The research was conducted in three locations in Malaysia: Kuala Lumpur, Petaling and Kota Kinabalu. Participants consisted of child protectors and rehabilitation officers from the Malaysia Welfare Department and medical social workers in hospitals. This paper presents an analysis of individual interviews in the three locations.A total of twenty-five interviews were conducted (twelve male, thirteen female; age range 29-51). Data were analysed using thematic analysis (Braun & Clarke, 2006).The research findings show that societal and professional cultures have influenced how child social workers express and regulate their emotions when dealing with clients.